Biomarkers of inflammation predict both vascular and non-vascular mortality in older men - Clarke, R; Emberson, J; Breeze, E; Casas, J; Parish, S; Hingorani, A; Fletcher, A; Collins, R; Smeeth, L (Oxford University Press, 2008)
Aims: To compare the predictive value of inflammatory biomarkers and lipids for vascular and non-vascular mortality in older men. Methods and results: The relevance of inflammatory biomarkers and lipids for vascular and non-vascular mortality was assessed in a prospective study of 5360 men (mean age 77 years) followed for 7 years. Vascular mortality was positively associated with log C-reactive protein (InCRP), fibrinogen and total/HDL0C (high-density lipoprotein cholesterol), and inversely associated with albumin [age adjusted hazard ratio (HR) per 2-SD higher usual level (approximately the difference between the top and the bottom thirds of the distribution): 2.09 for InCRP; 1.70 for fibrinogen; 0.50 for albumin and 1.45 for total/HDL-C]. The associations with the inflammatory markers were attenuated after adjustment for established risk factors, including lipids [adjusted HRs: 1.86 (InCRP); 1.44 (fibrinogen); 0.51 (albumin)], and further attenuated (and, for fibrinogen, no longer predictive) after adjustment for each other [fully adjusted HRs: 1.60 (InCRP); 1.01 (fibrinogen); 0.61 (albumin)]. Higher CRP and lower albumin levels were also associated with significantly raised non-vascular mortality independently of other characteristics [fully adjusted HRs: 1.62 (InCRP); 0.65 (albumin)]. Conclusion: In this cohort of older men, higher CRP and lower albumin levels strongly predicted both vascular and non-vascular mortality, independently of other characteristics.